2014
DOI: 10.1186/cc13980
|View full text |Cite
|
Sign up to set email alerts
|

Early adaptive immune suppression in children with septic shock: a prospective observational study

Abstract: IntroductionInnate immune suppression occurs commonly in pediatric critical illness, in which it is associated with adverse outcomes. Less is known about the adaptive immune response in critically ill children with sepsis. We designed a single-center prospective, observational study to test the hypothesis that children with septic shock would have decreased adaptive immune function compared with healthy children and that among children with sepsis, lower adaptive immune function would be associated with the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 35 publications
6
67
2
Order By: Relevance
“…Reduction in the ability of lymphocytes to produce interferon (IFN)-γ when incubated ex vivo with the lymphocyte stimulants phytohemagglutinin (PHA) or anti-CD3/anti-CD28 antibody has been associated with infections complications and death in the setting of pediatric and adult sepsis. 21, 22 These findings are in agreement with mRNA studies which suggest that early suppression of lymphocyte signaling pathways are associated with pediatric sepsis mortality. 23 Lastly, expression of co-inhibitory molecules such as programmed death (PD)-1 on lymphocytes, and its ligands PD-L1 and PD-L2 on antigen-presenting cells, is known to be upregulated in critically ill adults, with higher expression levels predicting adverse outcomes.…”
Section: Laboratory Characteristics Of Immunoparalysissupporting
confidence: 86%
See 1 more Smart Citation
“…Reduction in the ability of lymphocytes to produce interferon (IFN)-γ when incubated ex vivo with the lymphocyte stimulants phytohemagglutinin (PHA) or anti-CD3/anti-CD28 antibody has been associated with infections complications and death in the setting of pediatric and adult sepsis. 21, 22 These findings are in agreement with mRNA studies which suggest that early suppression of lymphocyte signaling pathways are associated with pediatric sepsis mortality. 23 Lastly, expression of co-inhibitory molecules such as programmed death (PD)-1 on lymphocytes, and its ligands PD-L1 and PD-L2 on antigen-presenting cells, is known to be upregulated in critically ill adults, with higher expression levels predicting adverse outcomes.…”
Section: Laboratory Characteristics Of Immunoparalysissupporting
confidence: 86%
“…19, 21 Muszynski et al demonstrated, in children with septic shock, that infectious complications were associated with lower lymphocyte counts and reduced ability of lymphocytes to respond to ex vivo stimulation with PHA. 22 This reduction was not limited to pro-inflammatory cytokines such as IFNγ but extended to anti-inflammatory cytokines as well, implying global down-regulation of cytokine responses. These data were consistent with transcriptome profiling done by Wong et al which suggested that early down-regulation of lymphocyte signaling pathways predicts mortality and organ failure duration in pediatric sepsis.…”
Section: Clinical Implications Of Immunoparalysismentioning
confidence: 99%
“…[39][40][41] The function of the remaining T cells is poor in some circumstances, with the degree of T-cell dysfunction predictive of adverse outcomes. [42][43][44] Lymphocytes can also express high levels of negative costimulatory cell surface molecules, such as programmed death (PD)-1, in critical illness. 45,46 These molecules, when ligated, promote apoptosis or cellular deactivation.…”
Section: Treatment-related Factorsmentioning
confidence: 99%
“…Prolonged lymphopenia, with absolute lymphocyte counts < 1,000 cells/mm 3 , has been reported to independently predict secondary infection and mortality risks in pediatric MODS (65). Autopsy studies have demonstrated marked lymphocyte apoptosis in lymphoid organs from nonsurvivors of sepsis-induced MODS (124,125). Reduced capacity of lymphocytes to produce pro-inflammatory cytokines such as interferon-γ and IL-2 has been associated with increased risk of infectious complications in septic children (126).…”
Section: Pamps and Dampsmentioning
confidence: 99%